2001
DOI: 10.1677/joe.0.1680465
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of insulin-like growth factor (IGF)-binding protein expression and secretion by adult human adrenocortical cells: differential regulation by IGFs and adrenocorticotropin

Abstract: In previous studies we have shown that IGF-II stimulates basal as well as ACTH-induced cortisol secretion from adult human adrenocortical cells more potently than IGF-I, and that both IGFs predominantly stimulate androgen biosynthesis. The steroidogenic effect of IGF-I and IGF-II is mediated through interaction with the IGF-I receptor, and modified by locally produced IGF-binding proteins (IGFBPs). In the present study, we identified and characterized IGFBP synthesis in normal adult human adrenocortical cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…In contrast, three out of four hormonally active ACCs showed strongly elevated specific IGF-I binding with a 3-4-fold increase in IGF-IR concentration, as compared with normal adrenocortical tissue [194]. H295R cells overexpress also IGFBP-2 [195], which accounts for only 12% of the IGFBP activity in normal adrenocortical cells, but seems to play a specific role in the progression of ACCs by modulating IGF-II activity [196]. In support of the hypothesis of a tumor-growth-promoting effect of IGFBP-2 is the observation that Y-1 mouse adrenocortical tumor cells overexpressing IGFBP-2 show increased tumorigenic potential and cell proliferation [197].…”
Section: Igf System Abnormalities In Specific Endocrine Cancer Andmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, three out of four hormonally active ACCs showed strongly elevated specific IGF-I binding with a 3-4-fold increase in IGF-IR concentration, as compared with normal adrenocortical tissue [194]. H295R cells overexpress also IGFBP-2 [195], which accounts for only 12% of the IGFBP activity in normal adrenocortical cells, but seems to play a specific role in the progression of ACCs by modulating IGF-II activity [196]. In support of the hypothesis of a tumor-growth-promoting effect of IGFBP-2 is the observation that Y-1 mouse adrenocortical tumor cells overexpressing IGFBP-2 show increased tumorigenic potential and cell proliferation [197].…”
Section: Igf System Abnormalities In Specific Endocrine Cancer Andmentioning
confidence: 99%
“…Treatment of adult human adrenocortical cells with ACTH predominantly stimulated the abundance of IGFBP-1 and to a lesser extent that of IGFBP-3, while IGF-I and IGF-II selectively induced the accumulation of IGFBP-3 and IGFBP-5 in the medium [205, 206]. Quantification of the specific bands by γ counting revealed that IGFBP-3 accounts for more than half of the detected IGFBP activity, followed by IGFBP-1 with 20% and IGFBP-4 with approximately 10% [196]. …”
Section: Igf System Abnormalities In Specific Endocrine Cancer Andmentioning
confidence: 99%
“…In adult human adrenocortical cells, both IGFs stimulate basal and ACTH-induced steroid biosynthesis by upregulating steroidogenic key enzymes and ACTH-receptor expression [5, 23 ± 24]. In analogy to the finding in fetal I time and dose -dependent stimulation of steroidbiosynthesis by IGF-I and -II [3,9 -11,12,85 -88,23,90,91] I predominant stimulation of androgen -secretion more potently by IGF-II than by IGF-I [4,6,8,23] I Stimulation of IGFBP -3, -4 and -5 expression and secretion by IGF-I and -II [6][7][8] I Differential modulation of IGF-induced steroidbiosynthesis by IGFBP-1 [89]…”
Section: The Insulin-like Growth Factor System In the Normal Adrenal mentioning
confidence: 99%
“…Development and function of the adrenal glands are markedly influenced by components of the IGF system (11)(12)(13)(14)(15). Besides IGF-I and -II, IGF-I receptors (IGF-IR), and IGF-II/mannose 6-phosphate receptors (IGF-II/ M6PR) (16,17), messenger RNA expression for all six high-affinity IGF binding proteins (IGFBPs) has been detected in fetal (18) and adult human adrenocortical tissue (18,19). Conditioned media of adrenal cells from various species were found to contain several IGFBPs (19 -22).…”
mentioning
confidence: 99%